2019
DOI: 10.1016/j.electacta.2019.06.161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water content and applied potential on the electrodeposition of Ni coatings from deep eutectic solvents

Abstract: Ni coatings were electrodeposited from 1:2 choline chloride (ChCl)-urea (U) deep eutectic solvents (DESs) on low carbon steel. We report on the interrelated influence of water content in the electrolyte and applied potential on the formation of Ni films and their chemical composition and morphology. This was investigated by cyclic voltammetry (CV) and chronoamperometry (CA) in combination with ex-situ characterization techniques (FE-SEM, EDS, XPS and Raman spectroscopy). Ni electrodeposition from DES is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…This will allow us to control the thickness and the morphology of the deposited layers precisely. 57 At a highly negatively charged surface (Fig. 3(a and h), s ¼ À0.32 C m À2 ), the number density prole as well as the water distribution close to the interface follows a completely different trend.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This will allow us to control the thickness and the morphology of the deposited layers precisely. 57 At a highly negatively charged surface (Fig. 3(a and h), s ¼ À0.32 C m À2 ), the number density prole as well as the water distribution close to the interface follows a completely different trend.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, this has been conrmed experimentally using combined electrochemical and surface analysis techniques. 56,57 On the other hand, in closed electrochemical systems, such as batteries and supercapacitors, high surface polarization leads to electrolysis of water in the vicinity of the electrode surface which results in formation of hydrogen and oxygen gas. Because of the gas formation, the internal pressure increases and the active site/pores of the electrode surface are blocked by the gas bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a residual water content leads to Ni and Ni(OH) 2(ads) . Lukaczynska et al [ 78 ] reported significant influence of water content on electrodeposition of Ni from ChCl:urea solutions. Higher than 4.5%wt water content enhances decomposition of the solvents at potentials lower than −0.9 V vs. Ag as quasi-reference electrode (QRE).…”
Section: Electrochemistry Of Targets Elementsmentioning
confidence: 99%
“…The strong influence of H 2 O on the viscosity and conductivity of the solvents has been reported in many occasions 15,[21][22][23] . More recently, it has also been shown that water affects the dynamics and the electrochemistry of active species 15,21,24,25 . In addition, computational modelling together with experimental techniques have shown that small amounts of H 2 O hydrate first the Cl − , and therefore strengthen the HBD-HBD and Ch + -HBD interactions 17,[26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…This has been described to happen for concentrations of H 2 O higher than 50 wt% 17,26,29 . As a result, a constant monitoring of the water content becomes mandatory for a proper understanding and use of DESs in many chemical [30][31][32] and electrochemical processes 17,21,24,25,33,34 .…”
Section: Introductionmentioning
confidence: 99%